Sharing Health-Related Data and Buddhism - Malcolm Voyce (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2023)
Health-related research funders, regulators and journals increasingly expect de-identified health research data to be shared widely. This article examines non-western reasons for decision-making in Thailand, a Buddhist country, to explore the extent to which Buddhist DACs should make decisions based on Buddhist norms. The method used in this study is a qualitative method with literature and sociology approaches. Meanwhile, the source of data came from the DAC and the perceptions of various Buddhists. The results of this study suggest that the social impact of big data on health has the support of Buddhists and the community so that there is data transparency that can be known by the wider community. In addition, health data is big data that can utilize technology in its management. In conclusion, data sharing raises concerns about the accuracy and reliability of data so that it needs supervision so that the data presented is the correct data.